2002
DOI: 10.1128/mcb.22.12.4218-4229.2002
|View full text |Cite
|
Sign up to set email alerts
|

RSC2, Encoding a Component of the RSC Nucleosome Remodeling Complex, Is Essential for 2μm Plasmid Maintenance in Saccharomyces cerevisiae

Abstract: The stable maintenance of the 2m circle plasmid depends on its ability to overcome intrinsic maternal inheritance bias, which in yeast normally results in the failure to transmit DNA molecules efficiently to daughter cells. In addition to the plasmid proteins Rep1 and Rep2 acting on the plasmid DNA locus STB, it is likely that other chromosomally encoded yeast proteins are required. We have isolated mutants of yeast unable to maintain 2m and found that RSC2 is essential for 2m to overcome maternal inheritance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
95
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 59 publications
14
95
1
Order By: Relevance
“…4C, lane 2). These data are consistent with the fact that, unlike the rsc2⌬ mutation, an rsc1⌬ mutation does not lead to an elevated loss of the 2m plasmid (34).…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…4C, lane 2). These data are consistent with the fact that, unlike the rsc2⌬ mutation, an rsc1⌬ mutation does not lead to an elevated loss of the 2m plasmid (34).…”
Section: Resultssupporting
confidence: 79%
“…A recent discovery by Wong et al (34) revealed a strong correlation between the nucleosome architecture at STB and the stable propagation of the 2m plasmid. In the absence of the Rsc2 protein, a component of one of the nucleosome remodeling complexes in yeast, there is a high rate of loss of the 2m circle (34). Concomitantly, there is a finite alteration of the chromatin structure of the STB region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors include the mitotic spindle, the spindleassociated motor Kip1, the RSC2 chromatin-remodeling complex, the centromere-specific histone H3-variant Cse4 (CenH3), and the yeast cohesin complex (9)(10)(11)(12)(13)(14)(15). The de novo assembly of the plasmid-partitioning complex at STB during the G1-S window of each cell cycle (9,12,14,16) is reminiscent of the assembly of the kinetochore complex at centromeres.…”
mentioning
confidence: 99%